2007
DOI: 10.1111/j.1537-2995.2007.01413.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bacterial inactivation in prestorage pooled, leukoreduced, whole blood–derived platelet concentrates suspended in plasma prepared with photochemical treatment

Abstract: These pilot experiments demonstrate inactivation of bacteria in PLTs suspended in plasma, suggesting that the PCT process may address contamination in conventional RDPs. Additional experiments with a wider range of bacteria and evaluation of PLT function in 100 percent plasma will be needed before implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In another related study, Brecher and colleagues 35 observed complete inactivation of four bacterial species in leukoreduced PLT concentrate pools containing up to 13.5 colony‐forming units per mL after amotosalen and UVA treatment. However, they did not explore the potential impact of the CAD on bacterial count.…”
Section: Discussionmentioning
confidence: 91%
“…In another related study, Brecher and colleagues 35 observed complete inactivation of four bacterial species in leukoreduced PLT concentrate pools containing up to 13.5 colony‐forming units per mL after amotosalen and UVA treatment. However, they did not explore the potential impact of the CAD on bacterial count.…”
Section: Discussionmentioning
confidence: 91%
“…Further, the platelet concentrates used in this study had lower residual plasma carryover than recommended by the manufacturer (32-47%). It is unlikely that the efficacy of the pathogen reduction process would be reduced by treating platelets outside of these limits, as the pathogen reduction function appears stable at a broad range of plasma carryover levels (Brecher et al, 2007;Liu et al, 2011). In addition, the units were incubated with the CAD for the longest allowable time (16 h), therefore representing a 'worstcase' scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Several validation studies of detection and reduction methods were carried out without showing the growth ability of the strains studied before treatment or without using untreated control bags as positive controls from the same donation to avoid false negative results [28–30]. In more recent studies, this new thinking is followed to demonstrate the growth ability of the strains in parallel using low inoculated control PC bags and estimation of the bacterial count during storage [31–35]. Especially, in the case of pathogen reduction methods, reliable results are crucial because one surviving organism may be able to proliferate again up to high counts and endanger the patient.…”
Section: Discussionmentioning
confidence: 99%